(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article explores the effectiveness of Task-Based Learning (TBL) as a pedagogical strategy for enhancing student engagement in multicultural classroom environments. In today’s increasingly globalized educational settings, learners often come from diverse cultural and linguistic backgrounds, which can present both challenges and opportunities for educators. The study examines how TBL promotes active participation, collaborative learning, and intercultural communication by focusing on real-world tasks that are meaningful to students. Drawing on recent empirical research, the paper highlights the positive effects of TBL on motivation, learner autonomy, and social interaction among students with varied cultural perspectives. The study also addresses potential difficulties in implementing TBL across cultures, including communication styles, prior learning experiences, and expectations. Practical recommendations for teachers and curriculum designers are provided to help integrate TBL effectively into multicultural contexts, thereby fostering inclusive, student-centered learning environments.